Determinants of environmental disclosures of listed firms in Ghana - Emerald Edem Welbeck; Godfred Matthew Yaw Owusu; Rita Amoah Bekoe; John Amoah Kusi (International Journal of Corporate Social Responsibility (JCSR), 2017)
The purpose of the paper is to examine the type of environmental-related information firms disclose mostly in Ghana, the trend of such disclosures and investigate the determinants of environmental disclosures by firms in Ghana. Using the Global Reporting Initiative (GRI) index as a benchmark, a content analysis of the corporate annual report of 17 firms listed on the Ghana Stock Exchange (GSE) was conducted over a 10-year period (2003 to 2012) to determine the total environmental disclosure scores of the sampled firms. The determinants of environmental disclosure practices of the firms were ascertained by means of a regression analysis. Results of this study indicate that listed firms in Ghana disclose some amount of environmentally-related information espoused by GRI though the level of disclosure is low. Also, the level of disclosure by environmentally-sensitive firms is higher than the less sensitive firms similar to existing studies. Moreover, the study finds firm size, auditor type, age of the firm and industry type to be significant predictors of firms' environmental disclosure practices.
Keywords: 650; Umweltbericht; Ghana